In vitro screening of taro varieties against Phytophthora leaf blight disease - govinda, padmaja (JOURNAL OF ROOT CROPS, 2016)
Four isolates of Phytophthora colocasiae causing leaf blight of Taro were collected from different Taro growing areas of Telangana and Andhra Pradesh and evaluated for their virulence on the 12 varieties. The ability of an isolate to cause disease symptoms across the varieties was interpreted as virulence. The disease reaction of 12 varieties showed differences in resistance to isolates of Phytophthora colocasiae. Variety RNCA-1 and Variety KCS-3 showed resistant reaction to all the isolates of Phytophthora colocasiae and Muktakeshi also showed similar reaction except to isolate PC2. Moderately resistant reaction was recorded by variety Kovvuru local to isolate PC1, PC2 and PC3. Variety NDC-1 showed susceptible reaction to three isolates viz, PC2, PC3 and PC4. Tenali, Hyderabad local, Jagtial local, Satamukhi, C-16, NDC-1, Kadma local varieties are shown susceptible to highly susceptible reaction to all the four isolates. Based on the resistant reaction two varieties i.e., KCS-3 and Mktakeshi are showing resistance reaction to all the isolates so by using of these varieties we can reduce the incidence of the blight disease of Taro.